A method for converting vertical graphene into diamond
By preparing an upright graphene film with monodispersed molybdenum atoms on a single crystal silicon substrate and converting it into diamond under low-pressure vacuum annealing conditions, the high energy consumption and high cost problems of diamond preparation under high temperature and high pressure conditions in the prior art are solved, and efficient preparation of diamond under low pressure is achieved.
Patent Information
- Application Number
- CN202310632157.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-31
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-05-31
AI Technical Summary
The prior art requires high temperature and high pressure conditions when preparing diamonds, high equipment requirements, high energy consumption, and limited resources, making it difficult to achieve efficient preparation under normal pressure or low pressure.
An upright graphene film with monodispersed molybdenum atoms was prepared on a single crystal silicon substrate by DC glow discharge plasma chemical vapor deposition method, and annealed in a tube furnace with a vacuum degree of 4-6Pa and 700-1100°C to achieve graphene conversion to diamond.
The phase transition process of graphene into diamond is realized under low pressure, reducing the preparation cost and energy consumption, and providing a new diamond preparation method.
Smart Images

Figure HDA0004258706720000011 
Figure HDA0004258706720000012 
Figure HDA0004258706720000021
Abstract
Description
Technical Field
[0001] The invention relates to a method for converting vertical graphene into diamond. Background Art
[0002] In the diamond structure, each carbon atom is arranged in sp 3 The hybrid orbital forms a covalent bond with the other four carbon atoms. This special crystal structure makes diamond have excellent properties such as high hardness, high thermal conductivity, high electron mobility and wide bandgap, and is widely used in many fields. However, the diamond resources in nature are limited and expensive. In contrast, artificial diamond has almost the same excellent properties, and the manufacturing cost is much lower than that of natural diamond. As we all know, high temperature and high pressure (HPHT) method and chemical vapor deposition (CVD) method are currently the commonly used methods for preparing high-purity, bulk single crystal diamond. The experimental conditions for the HPHT method to synthesize high-quality bulk single crystal diamond are extremely harsh. The pressure required for its phase change is as high as several thousand MPa or even higher, and the temperature conditions are also as high as several thousand degrees Celsius, and the preparation cost is high. The main preparation methods of CVD diamond include hot wire chemical vapor deposition (HFCVD), microwave plasma chemical vapor deposition (MPCVD), combustion flame chemical vapor deposition (CFCVD), etc., generally using gaseous carbon source as the raw material for diamond growth. In addition to using gaseous carbon sources, some researchers have used graphite plates as solid carbon sources and substrates, introduced hydrogen into MPCVD or HFCVD systems, and prepared diamonds on graphite, silicon substrates or multi-walled carbon nanotubes. The experimental principles of the above CVD methods all require the generation of gaseous CH in a gas atmosphere. X As a precursor for diamond growth, diamond is prepared. The conversion of solid carbon sources into gaseous carbon-containing active groups requires high input energy density, high equipment requirements, and high energy consumption. Therefore, developing a method for preparing diamonds at normal pressure or low pressure and at a lower temperature is of great significance to the diamond manufacturing industry.
[0003] Transition metal crystals can promote sp 3 Carbon is converted to sp 2Carbon is considered to be unfavorable for diamond growth and is used to prepare graphene. However, the inventors' previous studies found that graphene loaded with monodisperse tantalum atoms transforms into diamond under high-temperature annealing. This phase transition process is closely related to the outer valence electron orbital arrangement state and atomic radius of the tantalum atoms. At the same time, the inventors' theoretical calculation studies have shown that the effects of different transition metal dispersed single atoms on the phase transition barrier of graphene to diamond are quite different. Some transition metals such as Ag, Pt, Au, etc. have little effect on the phase transition barrier, that is, when graphite is loaded with this type of metal, it is still difficult to transform into diamond. Metal molybdenum is a metal that the inventors screened out in the calculation results that has a greater impact on the graphene / diamond phase transition barrier. However, no one has yet conducted experimental research on whether monodisperse metal molybdenum atoms can cause graphite to transform into diamond. Therefore, studying the effect of molybdenum on the graphite / diamond phase transition is of great significance for the development of methods for preparing diamond based on graphite. Summary of the invention
[0004] The object of the present invention is to provide a method for converting vertical graphene into diamond.
[0005] The technical solution adopted by the present invention is:
[0006] The present invention provides a method for converting vertical graphene into diamond, the method comprising:
[0007] (1) In a direct current glow discharge plasma chemical vapor deposition device, a pretreated single crystal silicon wafer is used as a substrate, molybdenum is used as an electrode, and methane and hydrogen are used as reaction gases to perform direct current glow discharge plasma chemical vapor deposition to obtain a vertical graphene film having monodispersed molybdenum atoms;
[0008] The conditions of the DC glow discharge plasma chemical vapor deposition are: the inflow rate of the methane is 40±3sccm (preferably 40sccm), the inflow rate of the hydrogen is 500±3sccm (preferably 500sccm), the pressure of the reaction chamber is 57±2Torr (preferably 57±0.1Torr), the power is 3.1-3.7kW (preferably 3.3±0.1kW), the temperature of the substrate is 930-970°C (preferably 950°C), and the deposition time is 55-65min (preferably 60min);
[0009] (2) placing the vertical graphene film having monodisperse molybdenum atoms prepared in step (1) in a tubular furnace, annealing at a vacuum degree of 4-6 Pa (preferably 5 Pa) and 700-1100° C. (preferably 700° C.) for 25-50 min (preferably 30 min), and converting the vertical graphene into diamond.
[0010] Furthermore, the pretreatment in step (1) is: cutting, grinding, and cleaning the single crystal silicon wafer. Specifically, in one embodiment of the present invention, the pretreatment is: using a diamond knife to cut the single crystal silicon wafer into pieces of 1×1 cm in size, grinding it back and forth on 1000-mesh sandpaper for 3-5 minutes, cleaning it with anhydrous ethanol, and drying it as a substrate for the growth of vertical graphene.
[0011] Preferably, in step (1), the conditions of the DC glow discharge plasma chemical vapor deposition are: the inflow rate of the methane is 40 sccm, the inflow rate of the hydrogen is 500 sccm, the pressure of the reaction chamber is 57±0.1 Torr, the power is 3.3±0.1 kW, the temperature of the substrate is 950°C, and the deposition time is 60 min. The temperature of the single crystal silicon wafer in step (1) is regulated by the power and pressure.
[0012] (1) Using a direct current glow discharge plasma chemical vapor deposition method (DC-CVD) with molybdenum as an electrode, a vertical graphene film with a thickness of about 3 μm having monodispersed molybdenum atoms is prepared on a single crystal silicon substrate; (2) Using a tube furnace vacuum annealing method, the vertical graphene obtained in step (1) is annealed. Annealing is performed in a tube furnace at a temperature of 700-1100° C. and a vacuum degree of 5 Pa for 30 minutes to obtain diamond.
[0013] In the step (1), the vertical graphene is prepared on a single crystal silicon substrate by a direct current glow discharge plasma chemical vapor deposition method using molybdenum as an electrode. Conventional direct current glow discharge plasma chemical vapor deposition equipment can be used. The thickness of the vertical graphene film prepared is required to be about 3 μm.
[0014] Further, the step (1) can be performed by the following steps: placing a single crystal silicon substrate into a DC glow discharge plasma chemical vapor deposition device, wherein the anode electrode and the cathode electrode are both high-purity metal molybdenum plates, and methane and hydrogen are used as reaction gases, with a gas ratio of CH 4 :H 2 =40sccm:500sccm, the reaction chamber pressure is 55-60Torr, the power is 3.2-3.5kW. The silicon wafer temperature is 950°C, the deposition time is 1 hour, and a vertical graphene film containing monodisperse molybdenum atoms with a thickness of about 3μm is prepared.
[0015] In the step (2), a tube furnace is used, the annealing temperature is 700-1100° C., the vacuum degree is 5 Pa, and the annealing time is 30 minutes to obtain diamond.
[0016] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in: (1) the preparation of graphene and the loading of metal molybdenum atoms are realized in a direct current glow discharge plasma chemical vapor deposition (DC-CVD) device; (2) compared with the phase change process of graphite to diamond in the high temperature and high pressure method, this method can be realized under low pressure and the phase change temperature is lower; the phase change can be realized using a low-cost tubular furnace; (3) it has very important scientific significance and value for the development of new diamond preparation methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is the XPS spectrum of the sample annealed at 700℃;
[0018] Figure 2 HRTEM image of the sample annealed at 700℃;
[0019] Figure 3 This is the XPS spectrum of the sample annealed at 900℃;
[0020] Figure 4 HRTEM image of the sample annealed at 900℃;
[0021] Figure 5 This is the XPS spectrum of the sample annealed at 1100℃;
[0022] Figure 6 HRTEM image of the sample annealed at 1100℃;
[0023] Figure 7 is the XPS spectrum of the sample before annealing;
[0024] Figure 8 HRTEM image of the sample before annealing; DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto:
[0026] Embodiment 1:
[0027] The prepared molybdenum-loaded vertical graphene film was annealed at 700°C. The single crystal silicon wafer was cut into 1×1 cm pieces with a diamond knife, and then the single crystal silicon wafer was pressed back and forth on 1000-grit sandpaper for 4 minutes; after the polishing, the treated silicon wafer was cleaned with anhydrous ethanol, and after the silicon wafer was dried, the single crystal silicon substrate was placed in a DC glow discharge plasma chemical vapor deposition device with molybdenum as the electrode, and methane and hydrogen were used as the reaction gas, with a gas ratio of CH 4 :H 2=40sccm:500sccm, the reaction chamber pressure is 57±0.1Torr, the power is 3.3±0.1kW, the silicon wafer temperature is 950°C, the deposition time is 60min, and a vertical graphene film with a thickness of about 3μm is prepared.
[0028] The grown vertical graphene was annealed in a tube furnace at a temperature of 700°C, a vacuum degree of 5 Pa, and a annealing time of 30 minutes.
[0029] For the samples annealed at 700℃, the carbon bonding state was analyzed by XPS spectrum, such as Figure 1 As shown in the figure, it can be seen that after high-resolution C1s spectrum fitting, five peaks are separated, and the binding energies are 284.8, 285.4, 286, 287.5 and 290.1 eV, representing sp 2 -C, sp 3 -C, CO, C=O bond and π-π* electronic transition peaks. The five peaks account for 51.16%, 29.81%, 13.15%, 4.69% and 1.19% respectively, sp 2 -C / sp 3 The -C ratio is 1.72. This indicates that after annealing at 700℃ for 30 minutes, there are more sp 3 -C.
[0030] The microstructure of the sample after annealing at 700℃ was analyzed by high-resolution transmission electron microscopy. Figure 2 As shown. The characterization area shows diamond (111) and (220) crystal planes. This indicates that there are more diamond structures in the sample, proving that the sp 3 -C is mainly diamond, which indicates that the molybdenum-supported vertical graphene is transformed into diamond after annealing.
[0031] Embodiment 2:
[0032] The prepared molybdenum-loaded vertical graphene film was annealed at 900°C. The single crystal silicon wafer was cut into 1×1 cm pieces with a diamond knife, and then the single crystal silicon wafer was pressed back and forth on 1000-grit sandpaper for 4 minutes; after the polishing, the treated silicon wafer was cleaned with anhydrous ethanol, and after the silicon wafer was dried, the single crystal silicon substrate was placed in a DC glow discharge plasma chemical vapor deposition device with molybdenum as the electrode, and methane and hydrogen were used as the reaction gas, with a gas ratio of CH 4 :H 2 =40sccm:500sccm, the reaction chamber pressure is 57±0.1Torr, the power is 3.3±0.1kW, the silicon wafer temperature is 950°C, the deposition time is 60min, and a vertical graphene film with a thickness of about 3μm is prepared.
[0033] The grown vertical graphene was annealed in a tube furnace at a temperature of 900°C, a vacuum degree of 5 Pa, and an annealing time of 30 minutes.
[0034] For the samples annealed at 900℃, the carbon bonding state was analyzed by XPS spectrum, such as Figure 3 As shown in the figure, it can be seen that after high-resolution C1s spectrum fitting, four peaks are separated, with binding energies of 284.8, 285.2, 286.3 and 287.3 eV, representing sp 2 -C, sp 3 -C, CO, C=O bonds. The four peaks account for 53.98%, 17.66%, 10.63% and 17.63% respectively, sp 2 -C / sp 3 The -C ratio is 3.04. This indicates that after annealing at 900℃ for 30 minutes, there are more sp 3 -C.
[0035] The microstructure of the sample after annealing at 900℃ was analyzed by high-resolution transmission electron microscopy. Figure 3 As shown, two different characterization areas are shown. Both areas show the relevant crystal plane information of diamond. This shows that there are more diamond structures in the sample, proving that more sp 3 -C is mainly diamond, which indicates that the molybdenum-supported vertical graphene is transformed into diamond after annealing.
[0036] Embodiment 3:
[0037] The prepared molybdenum-loaded vertical graphene film was annealed at 1100°C. The single crystal silicon wafer was cut into 1×1 cm pieces with a diamond knife, and then the single crystal silicon wafer was pressed back and forth on 1000-grit sandpaper for 4 minutes; after the polishing, the treated silicon wafer was cleaned with anhydrous ethanol, and after the silicon wafer was dried, the single crystal silicon substrate was placed in a DC glow discharge plasma chemical vapor deposition device with molybdenum as the electrode, and methane and hydrogen were used as the reaction gas, with a gas ratio of CH 4 :H 2 =40sccm:500sccm, the reaction chamber pressure is 57±0.1Torr, the power is 3.3±0.1kW, the silicon wafer temperature is 950°C, the deposition time is 60min, and a vertical graphene film with a thickness of about 3μm is prepared.
[0038] The grown vertical graphene was annealed in a tube furnace at a temperature of 1100°C, a vacuum degree of 5 Pa, and an annealing time of 30 minutes.
[0039] For the samples annealed at 1100℃, the carbon bonding state was analyzed by XPS spectrum, such as Figure 5 As shown in the figure, it can be seen that after high-resolution C1s spectrum fitting, four peaks are separated, with binding energies of 284.8, 285.3, 286.3 and 288.0 eV, representing sp 2 -C, sp 3 -C, CO and C=O bonds. The four peaks account for 45.37%, 21.33%, 13.84% and 19.45% respectively, sp 2 -C / sp 3 The -C ratio is 2.13. This indicates that after annealing at 1100℃ for 30 minutes, there are more sp 3 -C.
[0040] The microstructure of the sample after annealing at 1100℃ was analyzed by high-resolution transmission electron microscopy. Figure 6 As shown. Figure 6 It can be observed from the enlarged image (b) that the region shows diamond (111), (220) and (200) crystal planes. This indicates that there are more diamond structures in the sample, proving that the sp 3 -C is mainly diamond, which indicates that the molybdenum-supported vertical graphene is transformed into diamond after annealing.
[0041] Embodiment 4:
[0042] The single crystal silicon wafer was cut into pieces of 1×1 cm in size with a diamond knife, and then the single crystal silicon wafer was pressed and polished back and forth on 1000-grit sandpaper for 4 minutes; after polishing, the treated silicon wafer was cleaned with anhydrous ethanol, and after the silicon wafer was dried, the single crystal silicon substrate was placed in a DC glow discharge plasma chemical vapor deposition device with molybdenum as the electrode, and methane and hydrogen were used as the reaction gas, with a gas ratio of CH 4 :H 2 =40sccm:500sccm, the reaction chamber pressure is 57±0.1Torr, the power is 3.3±0.1kW, the silicon wafer temperature is 950°C, the deposition time is 60min, and a vertical graphene film with a thickness of about 3μm is prepared.
[0043] For the samples before annealing, XPS spectrum was used to analyze the carbon bonding state, such as Figure 7 As shown in the figure, it can be seen that after high-resolution C1s spectrum fitting, four peaks are separated, with binding energies of 284.8, 285.2, 286.2 and 288.2 eV, representing sp 2 -C, sp 3-C, CO and C=O bonds. The four peaks account for 48.75%, 20.99%, 11.08% and 19.17% respectively, sp 2 -C / sp 3 The -C ratio is 2.32. This indicates that there are more sp 3 -C.
[0044] The microstructure of the samples before annealing was analyzed by high-resolution transmission electron microscopy, such as Figure 8 As shown. It can be seen that the long strips of graphite are crisscrossed, and the more divergent amorphous phase information can be seen in the Fourier transform diagram. Regions 1 and 2 both show the graphite (002) crystal plane. Region 3 shows amorphous information. This shows that there are more amorphous phases in the sample, proving that the sp 3 -C is mainly an amorphous phase.
Claims
1. A method for converting vertical graphene into diamond, characterized in that The method is: (1) In a direct current glow discharge plasma chemical vapor deposition device, a pretreated single crystal silicon wafer is used as a substrate, molybdenum is used as an electrode, and methane and hydrogen are used as reaction gases to perform direct current glow discharge plasma chemical vapor deposition to obtain a vertical graphene film having monodispersed molybdenum atoms; The conditions of the DC glow discharge plasma chemical vapor deposition are: the inflow rate of the methane is 40±3sccm, the inflow rate of the hydrogen is 500±3sccm, the pressure of the reaction chamber is 57±2Torr, the power is 3.1-3.7kW, the temperature of the substrate is 930-970°C, and the deposition time is 55-65min; (2) placing the vertical graphene film having monodisperse molybdenum atoms prepared in step (1) in a tubular furnace, and annealing it at a vacuum degree of 4-6 Pa and a temperature of 700-1100° C. for 25-50 min to convert the vertical graphene into diamond.
2. The method for converting vertical graphene into diamond according to claim 1, characterized in that: The pretreatment described in step (1) is: cutting, grinding and cleaning the single crystal silicon wafer.
3. The method for converting vertical graphene into diamond as claimed in claim 2, characterized in that The pretreatment is as follows: using a diamond knife to cut the single crystal silicon wafer into pieces with a size of 1×1 cm, pressing and grinding it back and forth on 1000-mesh sandpaper for 3-5 minutes, washing it with anhydrous ethanol, and drying it.
4. The method for converting vertical graphene into diamond according to claim 1, characterized in that In step (1), the inflow rate of methane is 40 sccm.
5. The method for converting vertical graphene into diamond according to claim 1, characterized in that In step (1), the inflow rate of the hydrogen gas is 500 sccm.
6. The method for converting vertical graphene into diamond according to claim 1, characterized in that In step (1), the pressure of the reaction chamber is 57±0.1 Torr.
7. The method for converting vertical graphene into diamond according to claim 1, characterized in that In step (1), the power is 3.3±0.1 kW.
8. The method for converting vertical graphene into diamond according to claim 1, characterized in that: In step (1), the temperature of the substrate is 950° C. and the deposition time is 60 min.
9. The method for converting vertical graphene into diamond according to claim 1, characterized in that: In step (2), the annealing temperature is 700°C.
10. The method for converting vertical graphene into diamond according to claim 1, characterized in that: In step (2), the annealing time is 30 minutes.
Citation Information
Patent Citations
Foam diamond skeleton reinforced aluminum-based composite material and preparation method thereof
CN105671354A
Foam diamond skeleton reinforced copper-based composite and preparation method
CN105779805A